Karakteristik Responden Selama Pengambilan Darah Vena terhadap Tekanan Darah pada Anak - Yusi Nursiam; Mayetti Mayetti; Deswita Deswita (Jurnal Keperawatan Silampari, 2022)
This study aims to describe the characteristics of respondents during venous blood sampling on blood pressure in children. This type of research is observational research with a descriptive approach. The study results showed that the respondents who had normal blood pressure were school-age children, female, and the companion education was primary education (SD-SMP). Meanwhile, the pre-hypertension blood pressure of most school-age children of male and female gender with accompanying education is primary education. In conclusion, the description of respondents' characteristics during venous blood sampling on blood pressure in children is the majority of normal blood pressure with school-age children of male sex and companion education is primary education (SD-SMP). Keywords: Children, Gender; Venous Blood Draw, Blood Pressure